CURRENT POLICY ON HEPATITIS B VACCINATION AMONG TERTIARY CARE HOSPITAL HEMODIALYSIS PATIENTS - KHAN , RA; KHAN , ZA; SHAHZAD , M; GHANI , A; ALI , L (Biological and Clinical Sciences Research Journal, 2024)
A study was conducted at the Miangul Abdul Haq Jahanzeb Kidney Hospital in Swat to evaluate the vaccination status for hepatitis B among hemodialysis patients with chronic renal disease. The focus of the study was to determine the effectiveness of the hepatitis B vaccine in generating anti-HBS antibodies in this specific patient population. The primary objective was to identify and assess the hepatitis B vaccination status in patients undergoing hemodialysis due to chronic renal disease. This study aimed to determine the presence of anti-HBS antibodies in the patient's blood after receiving three or four doses of the 20-microgram hepatitis B vaccine between January 2022 and January 2023. The study followed a cross-sectional. The participants included hemodialysis patients with chronic renal disease. The validation of hepatitis B vaccination status was based on the measurement of the anti-HBS antibody titer in the patients' blood. This measurement was taken after administering three or four doses of the 20-microgram hepatitis B vaccine. A cut-off anti-HBS antibody titer of ≥10 IU/L was used to determine the effectiveness of the vaccination. The study included a total of 55 registered patients in the age range of 25 to 65 years. The average age of the patients was 48.70 ± 5.245 years. Among the participants, there was a ratio of 1.6:1, with 28 (25.7%) patients receiving three doses of the hepatitis B vaccination and 81 (72.2%) patients receiving four doses. The results indicated that 40 patients (50.2%) had confirmed vaccinations, as evidenced by an anti-HBS antibody titer of ≥10 IU/L. Patients with chronic kidney disease had a lower chance of developing anti-HBS antibodies with ≥ ten IU/L after hepatitis immunization. Individuals who get vaccinations early in the disease have a higher chance of developing advanced immunity.